Preface. Lecture Notes in Networks and Systems - Nguyen, T. D. L.; Le, A. N.; Verdú, Elena; Ganzha, M. (Springer Link, 2024)
The series “Lecture Notes in Networks and Systems” publishes the latest developments in Networks and Systems—quickly, informally and with high quality. Original research reported in proceedings and post-proceedings represents the core of LNNS.
Keywords: preface; lecture notes; networks; systems; Scopus